Pengaruh Penyaluran Kredit Perbankan Dan Tenaga Kerja Terhadap Produk Domestik Regional Bruto Sektor Pertanian Kabupaten/Kota Di Kalimantan Barat Periode 2010-2013 - B01110096, RIZA SOFIAN (Jurnal Curvanomic, 2016)
The title of this reseach is the effect of banking credit and labor to the regional Gros Domestic Product of agricultural sector on west borneo profince district/city 2010-2013 time priod. This research was aimed to understand how much the credit of agricultural sector and labor of agricultural sector effecting regional Gross Domestic product of Agricultural Sector in west borneo district/city on 2010-2013 time period. The analysis technique of this reseach is data panel multipel regresion. The data that used is secondary data from 2010-2013 that consist of 14 District/city in West borneo that got from BPS.The result of this reseach is the that credit of agricultural sector has a fositive significant effect to the regional Gross Domestic Product of agricultural sector with t-value 0,0000 or < 0,05. The labor of agricultural sector has positive significant effect to the regional Gross Domestic Product of agricultural sector with t-value 0,0000 < 0,05. Meanwhile simultaneosly from f statistic value is 1298.784 with probability value 0,000000 smaller than 0,05. This mean the regional Gross Domestic Product of agricultural sector simultaneously effected by credit of agricultural sector and labor of agricultural sector.Keywords: Banking credit,